Dietary Arginine Modulates Growth Performance, Hemato-Biochemical Indices, Intestinal Enzymes, Antioxidant Ability and Gene Expression of TOR and 4E-BP1 in Rainbow Trout, Oncorhynchus mykiss Fingerlings - Ahmed, Imtiaz; Ahmad, Ishtiyaq; Malla, Bashir Ahmad; Shah, Basit Amin; Wani, Zubair Ahmad; Khan, Younis Mohd (Frontiers in Marine Science, 2022)
We evaluated the effect of arginine on growth, hemato-biochemical variables, intestinal enzymes, antioxidant ability and expression of target of rapamycin (TOR) signaling pathway related genes in fingerling Oncorhynchus mykiss. A series of six uniform diets consisting of (450 g kg-1) protein and (20.9 g-1) of energy based diets with graduated levels (10.0, 12.5, 15.0, 17.5, 20.0 and 22.5 g kg-1) of arginine were formulated. Significant (p ˂ 0.05) variations were observed in various analyzed parameters. Growth parameters showed a positive linear trend with increasing arginine levels up to 17.5 g kg-1. Fish offered 17.5 g kg-1 dietary arginine exhibited highest body protein, lowest moisture and intermediate fat contents, whereas body ash content did not significantly (p ˃ 0.05) change with respect to each dietary arginine offered diet, except for the lowest levels. Each group also produced significant (p ˂ 0.05) changes in their hematological variables with maximum hemoglobin (Hb), hematocrit (Hct) content and red blood cell (RBC) count was noted at 17.5 g kg-1 arginine diet. Although majority of blood plasma parameters were insignificantly (p > 0.05) different with respect to varied arginine fed diets, however, plasma aspartate transaminase (AST) showed significant (p ˂ 0.05) variations across the treatments. Moreover, total protein, alkaline phosphatase (ALP) and albumin contents increased significantly (p ˂ 0.05) with increasing arginine concentrations up to 17.5 g kg-1 and thereafter a declined trend in these parameters were noted. Intestinal enzymes and antioxidant properties showed significant (p ˂ 0.05) variations, except plasma amylase, which showed insignificant variation. The maximum up-regulation of TOR and 4E-BP1 gene expression levels were found for fish fed 17.5 g kg-1 dietary arginine compared to the lower (10.0 and 12.5 g kg-1) and higher (20.0 and 22.5 g kg-1) arginine levels, which indicates that fish utilizes arginine more efficiently at this point. Quadratic regression analysis indicated the optimal arginine requirement of rainbow trout to be 17.61 g kg-1 of dry diet, corresponding to 39.13 g kg-1 of dietary protein, which enhances growth, immunity, antioxidant ability and also promote TOR signaling pathway in rainbow trout.